Legal Review of the Police Intelligence Authority in Handling Criminal Acts of Inter-Ethnic Conflict (Research Study in Merauke Regency, South Papua Province) - Nooryono, Makhsyar; Laksana, Andri Winjaya (UNISSULA Semarang, 2025)
This research is motivated by the high frequency of inter-ethnic conflicts in Merauke Regency, South Papua Province, which poses a serious threat to public security, social order, and human rights. These conflicts-such as the one between the Asmat and Mappi tribes-have resulted in fatalities, material losses, and widespread social damage. In the context of a state governed by law, the Indonesian National Police (Polri) holds a strategic responsibility to prevent and address potential social conflicts, one of which is carried out through the role of the Intelligence and Security Division (Intelkam) in conducting early detection and engagement to maintain national stability. This study aims to analyze the implementation of Polri's intelligence authority in handling criminal acts related to inter-tribal conflicts in Merauke Regency, as well as to identify the challenges encountered and propose alternative solutions. The research uses a socio-juridical approach with a descriptive-analytical specification. The data collected includes primary and secondary legal materials, as well as empirical data obtained through observation, interviews, and documentation. Qualitative analysis is applied to examine statutory provisions, institutional roles, and the social dynamics of indigenous communities in South Papua. The findings indicate that the exercise of Intelkam Polri's authority has been conducted in accordance with the applicable legal framework. However, it still faces several obstacles such as limited resources, cultural resistance, and weak inter-agency coordination. An optimal conflict resolution requires integration between formal legal approaches and cultural methods grounded in local wisdom. There is a pressing need to strengthen the capacity of Intelkam and to improve synergy among the government, traditional leaders, and local communities to achieve sustainable peace.